2021
DOI: 10.3389/fcvm.2021.752237
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Cardiac Biomarkers and Echocardiography in Critical COVID-19

Abstract: Background: Early risk stratification is crucial in critically ill COVID-19 patients. Myocardial injury is associated with worse outcome. This study aimed to evaluate cardiac biomarkers and echocardiographic findings in critically ill COVID-19 patients and to assess their association with 30-day mortality in comparison to other biomarkers, risk factors and clinical severity scores.Methods: Prospective, single-center, cohort study in patients with PCR-confirmed, critical COVID-19. Laboratory assessment included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…2, panel b). 11,30,31,33,34 A further sub-analysis performed stratifying the revised cohort according to the geographical location of enrolment revealed a higher prevalence of preexisting CAD among European cohorts (13.1%, 95% CI: 7.8-21.6%, P < 0.001, I 2 : 98.4%) followed by Asian (12.6%, 95% CI: 9.6-16.2%, I 2 : 93.0), and American patients (12.3%, 95% CI: 9.7-15.5%, I 2 : 58.7%) (Fig. 3, panels aÀc).…”
Section: Prevalence Of Preexisting Coronary Artery Disease In Coronav...mentioning
confidence: 99%
“…2, panel b). 11,30,31,33,34 A further sub-analysis performed stratifying the revised cohort according to the geographical location of enrolment revealed a higher prevalence of preexisting CAD among European cohorts (13.1%, 95% CI: 7.8-21.6%, P < 0.001, I 2 : 98.4%) followed by Asian (12.6%, 95% CI: 9.6-16.2%, I 2 : 93.0), and American patients (12.3%, 95% CI: 9.7-15.5%, I 2 : 58.7%) (Fig. 3, panels aÀc).…”
Section: Prevalence Of Preexisting Coronary Artery Disease In Coronav...mentioning
confidence: 99%
“…Zwaenepoel et al concludes that hs-TnI and NT-proBNP outperform other routinely used biomarkers (C-reactive protein, D-dimer and ferritin), as well as clinical indices of disease severity in ICU, such as total SOFA, respiratory SOFA and P/F ratio in critically ill COVID-19 patients [ 46 ]. Our data suggest that these cardiac biomarkers have similar utility in the case of mild and moderate forms of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were extended to patients with COVID-19, as numerous studies found significant associations between concentrations of (NT-pro)BNP upon hospital admission and subsequent clinical outcomes [70][71][72][73][74]. A representative single-center study from Spain included 396 COVID-19 patients presenting to the emergency department at a tertiary center during the first wave of the pandemic.…”
Section: Bnp/nt-probnpmentioning
confidence: 94%